Application of Information and Communication Technology in Citizenship Education Management - Dadang Mulyana (Jurnal Sosial Sains dan Komunikasi, 2023)
Application of Information and Communication Technology in Citizenship Education Management. This research aims to explore and analyze the application of Information and Communication Technology (ICT) in the context of educational management systems in educational institutions. This research uses a qualitative approach with descriptive methods. The research results show that the integration of Information and Communication Technology (ICT) in citizenship learning has a positive impact on students' learning experiences and teacher teaching effectiveness. Through the use of online platforms, simulation software, and online forums, students can engage in in-depth discussions, understand the implications of citizenship decisions through simulations, and increase their understanding of civic values. Training for teachers in the use of ICT also proves that adequate support and understanding of technology can improve the quality of civics learning. Thus, the research results confirm that ICT integration not only supports administrative efficiency, but also makes a significant contribution to the quality of education and the formation of students' civic character.